Osrednji simboli v Cankarjevem romanu Hiša Marije Pomočnice - Zupan Sosič, Alojzija (Jezik in slovstvo, 2022)
The article explores Cankar’s central symbols in the novel The Ward of Our Lady of Mercy, which have not yet been taken into account systematically. The interweaving of several literary directions and styles, i.e., realism, naturalism, decadence and symbolism, is referred to as syncretic symbolism, while the term for symbolistic correspondences of different perceptions and sensory and emotional impressions directed towards the spiritual experience of the world is symbolistic symbols. The following symbols are discussed: a hospital, a children’s collective, a door, white, Christ, eyes. These symbols are polyvalent; for example, in Christ as the entrance symbol to the novel, the large still eyes are exposed as a mirror of the soul, whereas Christ the Reformer at the end of the novel draws attention to the injustice of social conditions. Injustice is also criticised by pathological sexuality in the form of rape, paedophilia, incest and forced voyeurism, which is only characteristic of wealthy citizens.
Keywords: central symbols; children; Kristus; osrednji simboli; otroci; pathological sexuality; patološka seksualnost; sinkretični simbolizem; Slovene literature; slovenska književnost; syncretic symbolism